Numerical Simulation of Proppant Transportation and Placement Law In Fractured Coal Reservoirs - Chu, Xingyue (International Journal of Natural Resources and Environmental Studies, 2024)
Hydraulic fracturing technology has been widely used in the development of low-permeability oil fields, gas fields, and coalbed methane. The morphology of the sand dike formed by proppant deposition in the fracture determines the effective shape of the fracture, the effective volume, the flow conductivity, and the validity period of the fracture, and the research on the proppant transport law in the fracture is of great significance in optimizing the fracturing construction parameters and improving the fracturing production increase effect. In this paper, a systematic study on the proppant transport law in hydraulic fracturing fracture is carried out by numerical simulation, which reveals the mechanism of proppant settling and transport, clarifies the proppant transport and placement law under different working conditions, and puts forward the optimization strategy of hydraulic fracturing process on the basis of this study.